Copper-catalyzed direct couplings of terminal alkynes with primary and secondary benzyl bromides. Issue 12 (30th April 2019) - Zhang, Huiru; Sun, Nan; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan; Jin, Liqun
Abstract : We have developed a facile Cu-catalyzed benzylation of terminal alkynes from easily available benzyl bromides. Abstract : We have developed a facile Cu-catalyzed benzylation of terminal alkynes from easily available benzyl bromides. Both primary and secondary benzylic bromides have been successfully coupled with various aryl alkynes, alkyl alkynes and enynes, selectively affording benzyl alkynes in moderate to excellent yields. Examples of scale-up reactions as well as the application for preparing substituted allenes and phenanthrene have further demonstrated the practicality and efficiency of the developed strategy.